Understanding the Drivers of Food Waste in Malaysian Public Hospitals (MyHoFWa Study) - Samiun, Nurul Alia Aqilah; Razalli, Nurul Huda; Shahar, Suzana; Abdul Manaf, Zahara; Kefeli, Zurina; Jamhuri, Norshariza (Malaysian Journal of Medical Sciences, 2025)
Background: Understanding the perspectives and experiences of hospital food service personnel in managing food waste may aid in determining the factors that influence food waste. However, such research is still scarce globally. This study aimed to determine the factors influencing food wastage in Malaysian public hospitals.Methods: This qualitative research was performed in four Malaysian public hospitals and used purposive sampling to select participants for one-to-one interviews because of their role as key informants.Results: Themes such as patient culture and background, the quality and variety of food choices, the complexity of the ordering system, staff competency and attitude, environmental factors, treatment procedures, and patient clinical condition were identified using thematic analysis.Conclusion: Rather than focusing solely on patient experiences, this study explores other factors influencing food wastage in Malaysian public hospitals based on the experiences of hospital food services staff in managing food wastage.